A RECENT REVIEW ON NUTRIGENETICS AND NUTRIGENOMICS: CURRENT APPROACHES AND FUTURE ENDEAVORS (Contemporary Journal of Social Science Review, 2024)
The disciplines of nutrigenetics and nutrigenomics offer an in-depth knowledge for enhanced dietary counseling and recommendations to individuals, genetic subgroups, ethnic groups, and the general population as a whole. Thorough understanding of nutrition, biochemistry, genetics, Omic technologies has led to the application of preventative techniques for health improvement, preventing the onset of diseases, and reducing their severity. Research publications on Google Scholar, PubMed, Sci Hub, and the HEC digital library were examined.  87 publications that were pertinent to the topic were included in this study. The basic idea, technical terms, and technological advances of nutrigenomics and nutrigenetics are illustrated in this review, along with how this rapidly advancing knowledge can be applied to improve health, manage, and prevent disease, as well as the potential effects of changing nutritional and dietetic practices. As preventive medicine and nutrition grow more and more intertwined, it is crucial that dieticians, medical professionals, and geneticists receive the required training in the area of nutritional genomics in order to make the best use of its ideas and practices. Education must also be included in allied health courses so that students can teach the public about using omics technologies to improve healthcare.